Elastic deuteron-triton scattering AT 37MeV - Belyuskina, O.O.; Grantsev, V.I.; Davydovskyy, V.V.; Kisurin, K.K.; Omelchuk, S.E.; Palkin, G.P.; Roznyuk, Yu.S.; Rudenko, B.A.; Saltykov, L.S.; Semenov, V.S.; Slusarenko, L.I.; Struzhko, B.G.; et al. (Вопросы атомной науки и техники, 2009)
Results of measurement of differential cross section of elastic scattering of deuterons by tritons at the laboratory energy of 37 MeV for the center-of-mass angles θc.m. ranging from 25° to 150° are presented. The experiment is carried out on the U-240 isochronous cyclotron of the Institute for Nuclear Research, National Academy of Science of Ukraine. Obtained experimental data is analyzed theoretically in the framework of microscopic nuclear diffraction model. Angular distributions of deuterons in a region of the main maximum (θc.m. ≤ 60° ) are described quite well at deuteron energies of 14.4, 37.0 and 39.9 MeV . An explanation of a broad secondary maximum emerging at low deuteron energies is proposed using the phenomenological quasiclassical approximation. The quasiclassical approximation allows to describe the angular distributions only qualitatively at large angles 60° < θc.m. < 150°, where the cross sections are quite small. Представлено результати вимiрювання диференцiальних перерiзiв пружного розсiяння дейтронiв з енергiєю Ed = 37, 0 МеВ на тритонах у дiапазонi кутiв розсiяння 25° ≤ θc.m. ≤ 150° . Експеримент вико- нано на iзохронному циклотронi У-240 IЯД НАН України. Проведено теоретичний аналiз отриманих експериментальних даних в межах мiкроскопiчної дифракцiйної ядерної моделi. Кутовi розподiли дей- тронiв в областi головного максимуму (θc.m. ≤ 60° ) задовiльно описуються при енергiях дейтронiв 14, 4; 37, 0 та 39, 9 МеВ. Завдяки використанню феноменологiчного квазiкласичного наближення вдалося пояснити природу появи широкого вторинного максимуму при низьких енергiях дейтронiв. Квазiкла- сичне наближення дозволяє лише якiсно описати кутовi розподiли на великих кутах 60° ≤ θc.m. ≤ 150°, де перерiзи досить малi. Представлены результаты измерений дифференциальных сечений упругого рассеяния дейтронов с энергией Ed = 37 МэВ на тритонах в диапазоне углов рассеяния 25° ≤ θc.m. ≤ 150° . Эксперимент выполнен на изохронном циклотроне У-240 ИЯИ НАН Украины. Проведен теоретический анализ по- лученных экспериментальных данных в рамках микроскопической дифракционной ядерной модели. Угловые распределения дейтронов в области главного максимума (θc.m. ≤ 60°) достаточно хорошо описываются при энергиях дейтронов 14, 4; 37, 0 та 39, 9 МэВ. Предложено с использованием феменологического квазиклассического приближения объяснение появления широкого вторичного максимума при низких энергиях дейтронов. Квазиклассическое приближение позволяет лишь качественно описать угловые распределения на больших углах 60° ≤ θc.m. ≤ 150°, где сечения уже весьма малы.